Digital marketing tactics used in the profile of a political candidate: The case of the Costa Rica 2022 elections - Silva-Atencio, Gabriel (2023)
The use of digital marketing in the development of political strategies is increasingly common among the different political candidates running for public office, as it allows them to connect directly with the voter. However, the constant evolution of the digital era has changed the behavior patterns of voters, which is why the research question arises, seeking to identify the tactics used in the profile of the presidential candidate of the Partido Liberación Nacional (PLN), in the Facebook social network, during the month of January, 2022. This would determine whether the use of a political digital marketing strategy contributed to the results obtained. The approach was qualitative, so a review of the publications on the Internet was carried out to identify the strategy used, and to define the profiles that constitute the voting public. The most relevant finding was that the party did not develop a digital strategy according to the target population, as evidenced by the lack of specific content on Facebook, minimal interaction of the candidate with the social network, and lack of use of data analysis tools.